PENDUGAAN KEBERADAAN AIR TANAH DENGAN DATA GEOLISTRIK DI KAMPUNG ANGGORI KABUPATEN MANOKWARI - Ruth Grace Iriani Duwiri; Rosalina Rosina Mirino; Khristian Enggar Pamuji (Jurnal Natural, 2022)
Estimation of the presence and depth of groundwater is carried out using the Geoelectrical resistivity method with a dipole-dipole configuration consisting of 5 measuring lines. The results of the research are as follows on track 1 there is an aquifer with a depth of about 13-20 m and track 2 has an aquifer with a depth of about 25-50 m where both of these lines have an aquifer that flows to the Unipa Water Pump. Track 3 is interpreted to a depth of 50 m and the results cannot show the presence of groundwater with the lowest resistivity (????) value reaching 140 m. On track 4, the resistivity value (????) is 40 m and it is suspected that there is an aquifer with an estimated depth of >50 m. Track 4 has a stretch of 160 m so that geoelectrical data are interpreted to a depth of 50 m. Track 5 can be interpreted to a depth of 63 m and the interpretation results cannot indicate the presence of aquifers or groundwater.